Sustainability-based comparison of local bahareque and conventional reinforced concrete structural system for social housing construction - Alid Rocha-Tamayo; Natividad García-Troncoso; Natividad García-Troncoso; Irene Josa; Albert de la Fuente (Frontiers in Sustainable Cities)
IntroductionThe housing deficit necessitates government interventions, including social housing for vulnerable populations. This has led to diverse construction solutions that address homelessness while promoting local and traditional building methods. Beyond feasibility, sustainability is crucial.MethodsThis research evaluates the sustainability of two structural systems, bahareque and reinforced concrete, for low income housing in Ecuador using a multi-criteria decision-making model. Bahareque is a traditional construction system based on the use of Guadua cane, valued for its low environmental impact. The analysis was conducted through the Integrated Value Model for Sustainable Evaluation (MIVES), considering economic, environmental, and social factors. Indicators were defined through studies and expert surveys.ResultsThe analysis included material and construction costs, resource consumption, emissions, and social impacts like working conditions. Traditional and indigenous materials were also assessed for sustainability potential. Results showed bahareque had a sustainability index (SI) 17.5% higher than reinforced concrete.DiscussionThis framework can be adapted to different contexts and preferences by modifying its components and criteria.